Health Counseling on Triple Elimination (HIV/AIDS, Syphilis, And Hepatitis B) For Pregnant Women at Majelis Taklim Asyufi, Tanjung Barat Subdistrict, South Jakarta - Rosmawaty Lubis; Andi Julia Refiana (International Journal of Community Services, 2024)
Triple Elimination is a program held by the Ministry of Health of the Republic of Indonesia to overcome the transmission of HIV (Human Immunodeficiency Virus), Syphilis, and Hepatitis B from pregnant women to their babies. This activity was adopted from the World Health Organization (WHO) program called triple elimination. WHO believes that the transmission rate can be reduced to 5% from 15% with preventive activities in the form of testing for HIV, hepatitis B, and syphilis during antenatal care (ANC). Meanwhile, the Ministry of Health aims to reach zero by 2030 as written in the Regulation of the Minister of Health of the Republic of Indonesia number 52 of 2017. The activities carried out aim to increase public knowledge about health, especially about the Triple Elimination program (controlling the transmission of HIV/AIDS, Syphilis, and Hepatitis B) between pregnant women and their babies. By increasing public knowledge, it is hoped that people's attitudes and behavior will be able to change so they can live healthier lives. Pregnant women are willing to have themselves checked for these three diseases (HIV, Syphilis, and Hepatitis B) so that the incidence of disease can continue to be reduced. Health education activities regarding Triple Elimination (control of HIV/AIDS, Syphilis, and Hepatitis B) were carried out on Tuesday 31 October 2023 at Majelis Taklim Asyufi, Tanjung Barat Subdistrict, Jagakarsa District, South Jakarta. The target group is the women of the majelis taklim, numbering approximately 50 people. The counseling took place wisely, the mothers listened carefully. It is hoped that this outreach can increase public knowledge about health and reduce the incidence of HIV/AIDS, Syphilis, and Hepatitis B.